Pengaruh Pengetahuan Keuangan, Sikap Keuangan dan Kepribadian Terhadap Perilaku Manajemen Keuangan (Studi Kasus pada Pelaku UMKM Batik di Lampung) - Maidiana Astuti Handayani; Cici Amalia; Tri Darma Rosmala Sari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
In this study using primary data obtained directly from respondents and conducting survey and questionnaire methods. Based on the saturated sampling technique, there are 40 Batik SMEs as research samples. Data analysis method using multiple linear regression. The results of this study indicate that (1) there is a positive and significant influence of financial knowledge on financial management behavior in Batik SMEs in Lampung (2) there is a positive influence of financial attitudes on financial management behavior in Batik SMEs in Lampung (3) there is a negative influence of personality on financial management behavior in Batik SMEs in Lampung (4) there is a positive and significant influence on the behavior of financial management on Batik SMEs in Lampung